Optimizing HyFlex Learning: Pedagogical, Technological, and Policy Perspectives - Hidayati, Nur; Sindangsari, Laura Putri; Mustika, Nisa (Yayasan Sinergi Kawula Muda, 2025)
This narrative review explores the implementation, readiness, and impact of HyFlex (Hybrid-Flexible) learning models in higher education, a format increasingly adopted to support student-centered and technologically enriched learning. The objective is to synthesize empirical and conceptual literature to assess the model’s effectiveness and identify persistent challenges. Data was collected from Scopus, ERIC, Web of Science, and Google Scholar, using key phrases such as